Socialization on Agricultural Work from Farmer Parents to their Children: A Case Study - Gandasari, Dyah; P Lubis , Djuara; Dwidienawati, Diena (International Journal of Psychosocial Rehabilitation, 2020)
The declining number of farmers as agricultural human resources is one of the issues and challenges of the Indonesian agricultural sector. There is a declining trend of interest of the young generation in working in the agricultural sector. The interests and participation of youth in agriculture are encouraged by social and family factors. Their attitude is actually formed through socialization that comes from internal sources (parents, peers, and teachers). This article is limited to identifying the socialization by parents on agricultural work. The research analysis unit is young-adult individuals, which are farmer’s children at one vocational college in Indonesia. The sample was done purposefully. The selected respondents were 69 people. A descriptive statistical analysis was used with Microsoft Excel 2010. For better understanding, in-depth interviews were conducted on 3 cases using communication ethnography. The research result showed that most (75%) of the respondents’ parents talked about agriculture. The duration of conversation was around 10-60 minutes/month on the topics of cultivation, marketing, farmer status, and others. The responders were also involved in helping parents in agricultural activities, although their involvement was low (44%), moderate (31%), and high (9%). There was even 16% of youth who had never helped their parents on their farm.